2022
DOI: 10.3389/fimmu.2022.842653
|View full text |Cite
|
Sign up to set email alerts
|

CD33 Expression on Peripheral Blood Monocytes Predicts Efficacy of Anti-PD-1 Immunotherapy Against Non-Small Cell Lung Cancer

Abstract: Non-small cell lung carcinoma (NSCLC) is the leading cause of cancer-related deaths globally. Immune checkpoint blockade (ICB) has transformed cancer medicine, with anti-programmed cell death protein 1 (anti-PD-1) therapy now well-utilized for treating NSCLC. Still, not all patients with NSCLC respond positively to anti-PD-1 therapy, and some patients acquire resistance to treatment. There remains an urgent need to find markers predictive of anti-PD-1 responsiveness. To this end, we performed mass cytometry on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…3a-b ). CD33-expressing classical monocytes have previously been associated with anti-tumor immune responses and favourable responses to checkpoint inhibition in lung cancer 39 , and its blockade triggers spontaneous production of TNFα, IL-1b and IL-8 suggesting a repressive function in monocytes 40 . Expansion of CD33-expressing monocytes over CD33-negative monocytes in patients with Long COVID and elevated antibody responses ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a-b ). CD33-expressing classical monocytes have previously been associated with anti-tumor immune responses and favourable responses to checkpoint inhibition in lung cancer 39 , and its blockade triggers spontaneous production of TNFα, IL-1b and IL-8 suggesting a repressive function in monocytes 40 . Expansion of CD33-expressing monocytes over CD33-negative monocytes in patients with Long COVID and elevated antibody responses ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High absolute neutrophil counts as well as a high NLR can identify non-responders to immune checkpoint inhibition; a meta-analysis reported that a high NLR resulted in a worse PFS and OS in NSCLC, melanoma, and genitourinary cancer treated with ICI therapy [ 24 ]. First results have been reported also for monocytes; using CyTOF mass cytometry, Olingy et al described a link of CD33-high classical monocytes to the effectiveness of ICI therapy in NSCLC patients [ 25 ]. Using multi-color flow cytometry of blood from NSCLC patients undergoing ICI monotherapy, a high NLR, a high frequency of HLA-DR low monocytes, and low DC percentages were defined as adverse factors for clinical response and patients’ survival [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In female study participants, a higher rate of hyperprogression was observed by Kanjanapan and coworkers [ 61 ]. Olingy et al described a lower frequency of CD33high monocytes in the blood of female NSCLC patients and discussed a link to a reduced responsiveness to ICI therapy [ 25 ]. Comparing female and male patients in our cohort, female patients had a lower PD-L1 tumor expression, were more often never-smokers, and had more metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies ( n = 3) involving 172 NSCLC patients have found that high peripheral monocyte populations at baseline associate with improved response rates, and in some cases improved PFS and OS (Table 6 ). Specifically, Olingy and colleagues, in 26 stage III-IV NSCLC patients treated with anti-PD-1, evaluated the association between monocyte subsets (identified by mass cytometry) and clinical response [ 79 ]. Responders (R, with a decreased tumor size or SD > 6 months) had greater baseline frequencies of CD33 hi classical monocytes (CD33 hi cMo, p = 0.014) and CD9 + nonclassical monocytes (CD9 + nMo, p = 0.012) than non-responding (NR) patients (Fig.…”
Section: Circulating Immune Cellsmentioning
confidence: 99%